FORENSIC DETECTION OF CANNABINOIDS IN BIOLOGICAL FLUIDS: TECHNIQUES AND SENSITIVITY (International journal of artificial intelligence, 2025)
Forensic investigations often rely on the detection of cannabinoids in biological fluids to establish drug use and intoxication. While existing literature covers individual methods for cannabinoid analysis, a comprehensive guide detailing procedures for various sample types and their respective sensitivities remains absent. This study addresses this gap by presenting detailed protocols for isolating cannabinoids from saliva, blood, urine, and skin swabs. Extraction techniques with various solvents are employed, followed by thin-layer chromatography (TLC) for detection. The study demonstrates the effectiveness of urine as a readily accessible and informative sample for cannabinoid analysis. The TLC method boasts a sensitivity of 0.1 micrograms, providing a reliable means for identifying cannabinoids with high precision. These procedures and sensitivity data contribute significantly to advancing forensic science, offering valuable resources for practitioners and researchers in the field. The study emphasizes the importance of urine as a highly informative and readily accessible sample for cannabinoid analysis in forensic investigations. This comprehensive guide provides a valuable resource for forensic practitioners and researchers, contributing to the advancement of forensic science.